128 Clinical impact of changes in mitral regurgitation severity after optimization of medical therapy in heart failure: insights from BIOSTAT-CHF. (8th December 2021) - Pagnesi, Matteo; Adamo, Marianna; Sama, Iziah E.; Anker, Stefan D.; Cleland, John G.; Dickstein, Kenneth; Filippatos, Gerasimos S.; Inciardi, Riccardo M.; Lang, Chim C.; Lombardi, Carlo M.; Ng, Leong L.; Ponikowski, Piotr; et al.
Abstract: Aims: Few data are available regarding changes in mitral regurgitation (MR) severity with guideline-directed medical therapy (GDMT) in heart failure (HF). We evaluated the evolution and impact of MR after GDMT in the BIOlogy Study to TAilored Treatment in Chronic Heart Failure (BIOSTAT-CHF). Methods and results: A retrospective post hoc analysis was performed on HF patients from BIOSTAT-CHF with available data on MR status at baseline and at 9-month follow-up after GRMT optimization. The primary endpoint was a composite of all-cause death or HF hospitalization. Among 1022 patients with data at both time-points, 462 (45.2%) had moderate-severe MR at baseline and 360 (35.2%) had it at 9-month follow-up. Regression of moderate–severe MR from baseline to 9 months occurred in 192/462 patients (41.6%) and worsening from baseline to moderate–severe MR at 9 months occurred in 90/560 patients (16.1%). The presence of moderate-severe MR at 9 months, independent from baseline severity, was associated with an increased risk of the primary endpoint [unadjusted hazard ratio (HR), 2.03; 95% confidence interval (CI): 1.57–2.63; P  < 0.001], also after adjusting for the BIOSTAT-CHF risk-prediction model (adjusted HR: 1.85; 95% CI: 1.43–2.39; P  < 0.001). Younger age, LVEF ≥50% and treatment with higher ACEi/ARB doses were associated with a lower likelihood of moderate–severe MR at 9 months, whereas older age was the only predictor of worsening MR. Conclusions: Among patients with HF undergoing GDMT optimization, ACEi/ARB up-titration and HFpEF were associated with MR improvement, and the presence of moderate–severe MR after GRMT was associated with worse outcome.